Method for manufacturing chemically strengthened glass, chemically strengthened glass

CN123022647APending Publication Date: 2026-10-30AGC INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580021998.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-19
Filing Date
2025-03-18
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0036]根据本发明,能够提供一种能够得到具有更高的落下强度的化学强化玻璃的化学强化玻璃制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

Provided is a method for producing chemically strengthened glass. A method for producing chemically strengthened glass, which is a method for producing chemically strengthened glass by immersing a glass for chemical strengthening in a molten salt, wherein the molten salt contains sulfate ions, and the content of the sulfate ions in the molten salt is 1.35% by mass or more relative to the total mass of the molten salt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for manufacturing chemically strengthened glass. More specifically, it relates to a method for manufacturing chemically strengthened glass by immersing chemically strengthened glass in molten salt.

[0002] In addition, the present invention relates to chemically strengthened glass. Background Technology

[0003] In recent years, protective glass has been used to protect display devices such as mobile phones, smartphones, and tablets, as well as to improve their aesthetics. For these applications, protective glass requires excellent strength to prevent breakage caused by impacts and other factors.

[0004] It is known that methods for improving the surface strength of glass can be achieved by chemically strengthening it by immersing it in molten potassium nitrate salts. For example, Patent Document 1 discloses a lithium aluminum silicate glass that achieves a relatively large surface compressive stress layer and compressive stress layer depth through a two-step chemical strengthening process. Patent Document 1 describes how, by using sodium salt in the first step and potassium salt in the second step, the lithium aluminum silicate glass can increase surface stress and stress layer depth while suppressing tensile stress generated inside the chemically strengthened glass.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Publication No. 2013-520388 Summary of the Invention

[0008] The problem that the invention aims to solve

[0009] In recent years, there has been a demand for further improvements in the strength of protective glass. Protective glass for portable devices sometimes cracks due to deformation upon impact, and there is a requirement for protective glass to withstand drops from higher heights without breaking (possessing higher drop strength).

[0010] The inventors studied the protective glass described in Patent Document 1 and found that there is room for improvement in terms of drop strength.

[0011] The present invention was made in view of the above-mentioned problems, and its objective is to provide a method for manufacturing chemically strengthened glass that can produce chemically strengthened glass with higher drop strength.

[0012] In addition, the present invention also aims to provide a chemically strengthened glass.

[0013] means for solving problems

[0014] The inventors conducted in-depth research on the above-mentioned problems and found that the problems could be solved by adjusting the sulfate ion content in the molten salt, thus completing the present invention.

[0015] That is, the inventors discovered that the above problems can be solved by the following configuration.

[0016] [1] A method for manufacturing chemically strengthened glass, wherein the method is a method for manufacturing chemically strengthened glass by immersing chemically strengthened glass in molten salt, wherein the molten salt contains sulfate ions and the content of sulfate ions in the molten salt is 1.35% by mass or more relative to the total mass of the molten salt.

[0017] [2] According to the chemically strengthened glass manufacturing method of [1], wherein the molten salt comprises: sulfate, and one or more selected from the group consisting of nitrate, nitrite, sulfite, carbonate, phosphate and halide salt.

[0018] [3] According to the chemically strengthened glass manufacturing method of [2], wherein the molten salt comprises the nitrate and the sulfate.

[0019] [4] The chemically strengthened glass manufacturing method according to [2] or [3], wherein the sulfate comprises at least one selected from the group consisting of lithium sulfate, sodium sulfate and potassium sulfate.

[0020] [5] The chemically strengthened glass manufacturing method according to any one of [1] to [4], wherein the molten salt substantially does not contain salt in a solid state.

[0021] [6] The chemically strengthened glass manufacturing method according to any one of [1] to [5], wherein the content of sulfate ions in the molten salt is 5.00% to 24.00% by mass relative to the total mass of the molten salt.

[0022] [7] The chemically strengthened glass manufacturing method according to any one of [1] to [6], wherein the value of the sulfate ion content in the molten salt is set to C. SO4 When the temperature of the molten salt is set to T, the following equation (1) is satisfied: Equation (1) 0.0215T-4.0124≤C SO4 ≤0.0720T-8.4000 In equation (1), the unit of T is °C. It should be noted that the value of T is above 200. In equation (1), C SO4 The unit is mass%, C SO4The value is the content of sulfate ions relative to the total mass of the molten salt.

[0023] [8] The chemically strengthened glass manufacturing method according to any one of [1] to [7], wherein, before and after immersing the chemically strengthened glass in the molten salt, when the element with the largest increase in concentration in the molten salt is selected as a specific alkali element, the content of the specific alkali element in the molten salt is 1 ppm to 50,000 ppm by mass relative to the total mass of the molten salt.

[0024] [9] The chemically strengthened glass manufacturing method according to any one of [1] to [8], wherein the molten salt comprises two or more salts selected from the group consisting of lithium salts, sodium salts and potassium salts.

[0025]

[10] The chemically strengthened glass manufacturing method according to any one of [1] to [9], wherein the molten salt comprises two or more salts selected from the group consisting of lithium nitrate, sodium nitrate and potassium nitrate, and the molten salt further comprises one or more salts selected from the group consisting of sodium sulfate and potassium sulfate.

[0026]

[11] The chemically strengthened glass manufacturing method according to any one of [1] to

[10] , wherein the molten salt comprises sodium nitrate and the ratio of potassium nitrate content to sodium nitrate content by mass is 0.00 to 24.00.

[0027]

[12] The chemically strengthened glass manufacturing method according to any one of [1] to

[11] , wherein the molten salt comprises sodium nitrate and the ratio of potassium nitrate content to sodium nitrate content by mass is 0.25 to 9.00.

[0028]

[13] The chemically strengthened glass manufacturing method according to any one of [1] to

[12] , wherein the molten salt comprises sodium nitrate and the ratio of potassium nitrate content to sodium nitrate content by mass is 0.42 to 2.34.

[0029]

[14] The method for manufacturing chemically strengthened glass according to any one of [1] to

[13] , wherein the chemically strengthened glass comprises silicon, aluminum and lithium.

[0030]

[15] A method for manufacturing chemically strengthened glass, wherein the molten salt after the chemically strengthened glass manufacturing method described in

[14] is further cooled to precipitate a specific metal salt containing lithium while maintaining the molten state of the molten salt, and a molten salt regeneration process is performed to recover the specific metal salt from the molten salt in the molten state to obtain a regenerated molten salt, and a chemically strengthened glass is immersed in the regenerated molten salt to perform a chemical strengthening process.

[0031]

[16] In the chemically strengthened glass manufacturing method according to

[15] , when obtaining the regenerated molten salt, sulfate is added to the molten salt after the specific metal salt is recovered.

[0032]

[17] A method for manufacturing chemically strengthened glass, wherein the regenerated molten salt after the chemically strengthened glass manufacturing method described in

[15] or

[16] is alternately subjected to molten salt regeneration treatment and chemical strengthening treatment.

[0033]

[18] A chemically strengthened glass, wherein, Let the hydrogen concentration at a depth of 0.5 μm, measured from the outermost surface of the chemically strengthened glass, be C. H (0.5) Set the hydrogen concentration at a depth of 0.98 μm as C. H When (0.98), R is calculated by the following formula (H1). H Below 2.00 Formula (H1) R H =C H (0.5) / C H (0.98) In equation (H1), C H (0.5) and C H The units of (0.98) are 10 20 atoms / cm 3 .

[0034]

[19] A chemically strengthened glass, wherein, Let the hydrogen concentration at a depth of 0.6 μm, measured from the outermost surface of the chemically strengthened glass, be C. H (0.6) Set the hydrogen concentration at a depth of 0.8 μm as C. H When (0.8), S is calculated by the following formula (H2). H Above -0.40 Formula (H2) S H =(C H (0.8)-C H (0.6)) / 0.2 In equation (H2), C H (0.8) and C H The units of (0.6) are 10. 20 atoms / cm 3 .

[0035] Invention Effects

[0036] According to the present invention, a method for manufacturing chemically strengthened glass that can obtain chemically strengthened glass with higher drop strength can be provided.

[0037] In addition, according to the present invention, a chemically strengthened glass can also be provided. Detailed Implementation

[0038] The chemically strengthened glass manufacturing method of the present invention will be described in detail below. However, the present invention is not limited to the following embodiments and can be implemented in any modified form without departing from the spirit of the present invention.

[0039] In this specification, the glass composition is expressed as a mole percentage based on oxides, and is sometimes abbreviated as %. Additionally, the "~" indicating a numerical range is used to encompass the values ​​preceding and following it as lower and upper limits.

[0040] In glass composition, "substantially not containing" means not containing any components other than unavoidable impurities contained in raw materials, etc., that is, not intentionally containing any components. Specifically, regarding components other than those described as part of the glass composition, for example, it is preferably less than 0.1 mol%, more preferably less than 0.08 mol%, and even more preferably less than 0.05 mol%.

[0041] In this specification, "chemically strengthened glass" refers to glass that has undergone chemical strengthening treatment. Conversely, "chemically strengthened glass" refers to glass before undergoing chemical strengthening treatment.

[0042] In this specification, examples of salts contained in molten salts, unless otherwise specified, refer to salts used as raw materials in the preparation of molten salts.

[0043] In addition, unless otherwise specified in this specification, the content and ratio of the components in the molten salt each represent the content and ratio of the components of the raw materials used in the preparation of the molten salt.

[0044] <Methods for Manufacturing Chemically Strengthened Glass>

[0045] The chemically strengthened glass manufacturing method of the present invention is a method of manufacturing chemically strengthened glass by immersing chemically strengthened glass in molten salt, wherein the molten salt contains 1.35% by mass or more sulfate ions relative to the total mass of the molten salt.

[0046] According to the chemically strengthened glass manufacturing method of the present invention, chemically strengthened glass with higher drop strength can be obtained. The mechanism is not necessarily determined, but the inventors speculate as follows.

[0047] When chemically strengthened glass is immersed in molten salt for chemical strengthening, an exchange of ions occurs between the glass and the molten salt. It is believed that sulfate ions strongly attract components from the glass, and the activity of ions exchanged from the glass is easily reduced by sulfate ions. Therefore, promoting ion exchange during chemical strengthening is considered essential.

[0048] As a result, it is believed that the chemically strengthened glass manufacturing method according to the present invention can produce chemically strengthened glass with higher drop strength.

[0049] The chemically strengthened glass and molten salt used in the chemically strengthened glass manufacturing method of the present invention will be described in detail below.

[0050] Chemically strengthened glass

[0051] The chemically strengthened glass used in the chemically strengthened glass manufacturing method of the present invention is not particularly limited, but preferably contains lithium, and more preferably contains silicon, aluminum and lithium.

[0052] The preferred method for chemically strengthened glass is described below.

[0053] It should be noted that the preferred composition of chemically strengthened glass (hereinafter also referred to as "matrix glass composition") will be described below.

[0054] The matrix glass composition preferably includes Li (lithium), and more preferably is an aluminosilicate glass containing Li, Si (silicon) and Al (aluminum).

[0055] As a matrix glass composition, more specifically, it preferably contains, in molar percentage based on oxides: 52% to 75% SiO2, 8% to 20% Al2O3, and 5% to 16% Li2O.

[0056] The preferred matrix glass composition will be described below. It should be noted that, for example, the content of SiO2 as a molar percentage based on oxides will sometimes be described as "[SiO2]".

[0057] SiO2 is a component that forms the glass framework. In addition, SiO2 is a component that improves chemical durability and reduces the formation of cracks when damage occurs on the glass surface.

[0058] The SiO2 content is preferably 52% or more, more preferably 55% or more, and particularly preferably 60% or more. On the other hand, from the viewpoint of improving meltability, the SiO2 content is preferably 75% or less, more preferably 72% or less, more preferably 70% or less, and particularly preferably 68% or less.

[0059] From the perspective of improving ion exchange performance during chemical strengthening and increasing surface compressive stress after strengthening, Al2O3 is an effective component.

[0060] The Al2O3 content is preferably 8% or more, more preferably 9% or more, even more preferably 10% or more, particularly preferably 11% or more, and typically 12% or more. On the other hand, when the Al2O3 content is too high, crystals tend to grow easily during melting, which can easily lead to a decrease in yield due to devitrification defects. In addition, the viscosity of the glass increases and its meltability decreases. The Al2O3 content is preferably 20% or less, more preferably 19% or less, and even more preferably 18% or less.

[0061] Both SiO2 and Al2O3 are components that stabilize the structure of glass. In order to reduce brittleness, the total content of SiO2 and Al2O3 is preferably 65% ​​or more, more preferably 70% or more, and even more preferably 75% or more.

[0062] Li₂O is a component that generates surface compressive stress through ion exchange and improves the meltability of glass. By including Li₂O in the matrix glass composition, surface compressive stress can be introduced by exchanging lithium ions on the glass surface for sodium ions, and further exchanging sodium ions for potassium ions. From the viewpoint of easily obtaining an optimal stress distribution, the Li₂O content is preferably 5% or more, more preferably 7% or more, further preferably 9% or more, particularly preferably 10% or more, and most preferably 11% or more.

[0063] On the other hand, when the Li2O content is too high, the crystal growth rate during glass forming increases, sometimes leading to a significant decrease in yield due to devitrification defects. The Li2O content is preferably 20% or less, more preferably 16% or less, even more preferably 14% or less, and particularly preferably 12% or less.

[0064] Neither Na₂O nor K₂O is essential, but both are components that improve the meltability of glass and reduce the crystal growth rate. To improve ion exchange performance, it is preferable that the combined content of Na₂O and K₂O is 2% or more. Furthermore, the combined content of Na₂O and K₂O is preferably 10% or less, more preferably 9% or less, more preferably 8% or less, further preferably 7% or less, and particularly preferably 5% or less.

[0065] Na₂O is a component that forms a surface compressive stress layer during chemical strengthening treatment using potassium salts, and it is also a component that can improve the meltability of glass. To achieve this effect, the Na₂O content is preferably 1% or more, more preferably 2% or more, further preferably 3% or more, and particularly preferably 4% or more. On the other hand, from the viewpoint of avoiding a decrease in surface compressive stress (CS) during strengthening treatment using sodium salts, and from the viewpoint of increasing internal compressive stress, the Na₂O content is preferably 8% or less, more preferably 7% or less, further preferably 6% or less, and particularly preferably 5% or less.

[0066] K₂O may be included to improve ion exchange performance. When K₂O is included, its content is preferably 0.1% or more, more preferably 0.15% or more, and particularly preferably 0.2% or more. To further prevent devitrification, the K₂O content is preferably 0.5% or more, more preferably 1.2% or more. On the other hand, a large amount of K can sometimes become a major cause of brittleness and a decrease in surface stress due to reverse exchange during strengthening; therefore, the K₂O content is preferably 5% or less, more preferably 3% or less.

[0067] The total content R of Li₂O, Na₂O, and K₂O is preferably 5% or more, more preferably 8% or more, even more preferably 10% or more, and particularly preferably 12% or more. The aforementioned R is preferably 25% or less, more preferably 20% or less.

[0068] From the viewpoint of further improving the chemical strengthening properties against compressive stress in deep layers, the content of Li2O relative to the aforementioned ratio of R ([Li2O] / ([Li2O]+[Na2O]+[K2O]), hereinafter also referred to as "Li2O / R2O") is more preferably 0.52 or more, and even more preferably 0.55 or more. From the viewpoint of further improving chemical durability, the Li2O / R2O ratio is more preferably 0.80 or less, even more preferably 0.78 or less, and particularly preferably 0.75 or less.

[0069] From the viewpoint of further improving the chemical strengthening properties against compressive stress in deep layers, the ratio of Na₂O content to R ([Na₂O] / ([Li₂O]+[Na₂O]+[K₂O]), hereinafter also referred to as "Na₂O / R₂O") is preferably 0.05 or more, more preferably 0.08 or more, and even more preferably 0.10 or more. From the viewpoint of further improving chemical durability, Na₂O / R₂O is preferably 0.60 or less, more preferably 0.50 or less, even more preferably 0.40 or less, and particularly preferably 0.30 or less.

[0070] From the viewpoint of further improving the resistivity of the glass, the K2O content relative to the aforementioned R ratio ([K2O] / ([Li2O]+[Na2O]+[K2O]), hereinafter also referred to as "K2O / R2O") is preferably 0.05 or more, more preferably 0.08 or more, and even more preferably 0.10 or more. From the viewpoint of further improving the chemical strengthening properties against compressive stress near the surface, the K2O / R2O ratio is preferably 0.50 or less, more preferably 0.40 or less, even more preferably 0.30 or less, and particularly preferably 0.20 or less.

[0071] Furthermore, from the viewpoint of suppressing the rise in devitrification temperature, the product of Li₂O / R₂O, Na₂O / R₂O, and K₂O / R₂O is preferably 0.005 or more, more preferably 0.008 or more, and even more preferably 0.010 or more. Additionally, from the viewpoint of improving chemical properties, the above product is preferably 0.030 or less, more preferably 0.028 or less.

[0072] The content of Al2O3 relative to the aforementioned ratio of R ([Al2O3] / [Li2O]+[Na2O]+[K2O], hereinafter also referred to as "Al2O3 / R2O") is preferably 0.20 or more, more preferably 0.30 or more, even more preferably 0.40 or more, and even more preferably 0.50 or more. The Al2O3 / R2O ratio is preferably 0.90 or less, more preferably 0.88 or less, and even more preferably 0.85 or less.

[0073] To reduce viscosity during melting, MgO may be included. The MgO content is preferably 0.5% or more, more preferably 1% or more, further preferably 2% or more, and particularly preferably 3% or more. On the other hand, if the MgO content is too high, it may be difficult to increase the compressive stress layer during chemical strengthening treatment. The MgO content is preferably 15% or less, more preferably 10% or less, further preferably 8% or less, and particularly preferably 6% or less.

[0074] While ZrO2 may not be present, its presence is preferred from the viewpoint of increasing the surface compressive stress of chemically strengthened glass. The ZrO2 content is preferably 0.1% or more, more preferably 0.15% or more, even more preferably 0.2% or more, particularly preferably 0.25% or more, and typically 0.3% or more. On the other hand, excessive ZrO2 content can easily lead to devitrification defects, and sometimes makes it difficult to increase the compressive stress value during chemical strengthening treatment. The ZrO2 content is preferably 2% or less, more preferably 1.5% or less, even more preferably 1% or less, and particularly preferably 0.8% or less.

[0075] The Y2O3 content is preferably 0.1% or more, more preferably 0.2% or more, even more preferably 0.5% or more, and particularly preferably 1% or more. On the other hand, if the Y2O3 content is too high, it may be difficult to increase the compressive stress layer during chemical strengthening treatment. The Y2O3 content is preferably 5% or less, more preferably 3% or less, even more preferably 2% or less, and particularly preferably 1.5% or less.

[0076] The composition (matrix glass composition) of the chemically strengthened glass supplied for chemical strengthening is preferably the composition described above.

[0077] There are no particular limitations on the method for obtaining chemically strengthened glass with a matrix glass composition, and known methods can be used. For example, to obtain glass with the above composition, the glass raw materials are appropriately prepared, heated and melted in a glass melting furnace, and then homogenized by bubbling, stirring, adding a clarifying agent, etc., forming a glass sheet of a specified thickness, and then slowly cooling it. Alternatively, it can be formed into a sheet by forming it into a block, slowly cooling it, and then cutting it.

[0078] Methods for forming glass sheets include, for example, float glass, pressing glass, fusion glass, and drawing glass. Float glass is particularly preferred when manufacturing large glass sheets. Continuous forming methods other than float glass, such as fusion glass and drawing glass, are also preferred.

[0079] Furthermore, the chemically strengthened glass can be a glass-ceramic. When the chemically strengthened glass is a glass-ceramic, it is preferable to have a glass-ceramic containing one or more crystals selected from the group consisting of lithium silicate crystals, lithium aluminosilicate crystals, and lithium phosphate crystals. As lithium silicate crystals, lithium metasilicate crystals and lithium disilicate crystals are preferred. As lithium phosphate crystals, lithium orthophosphate crystals are preferred. As lithium aluminosilicate crystals, β-spodumene crystals and petalite crystals are preferred.

[0080] From the viewpoint of improving mechanical strength, the crystallinity of the glass-ceramic is preferably 10% or more, more preferably 15% or more, further preferably 20% or more, and particularly preferably 25% or more. Furthermore, to improve transparency, it is preferably 90% or less, more preferably 70% or less, even more preferably 60% or less, and further preferably 50% or less. A lower crystallinity also provides advantages in terms of ease of bending and shaping by heating. The crystallinity can be calculated from X-ray diffraction intensity using the Riedbold method. The Riedbold method is described in the *Crystal Analysis Handbook* (Kyoritsu Publishing, 1999, pp. 492-499), edited by the Editorial Committee of the *Crystal Analysis Handbook* of the Crystallographic Society of Japan.

[0081] To improve transparency, the average particle size of the precipitated crystals in the glass-ceramic is preferably 300 nm or less, more preferably 200 nm or less, even more preferably 150 nm or less, and particularly preferably 100 nm or less. The average particle size of the precipitated crystals can be determined from transmission electron microscopy (TEM) images. Alternatively, it can be estimated from scanning electron microscopy (SEM) images.

[0082] The Young's modulus of chemically strengthened glass is preferably 80 GPa or higher, and more preferably 83 MPa or higher.

[0083] In addition, the fracture toughness value (K) of chemically strengthened glass IC The preferred value is 0.70 MPa·m 1 / 2 The above, more preferably 0.75 MPa·m 1 / 2 The above is further preferably 0.80 MPa·m 1 / 2 The above. Fracture toughness value K IC Mostly 2.00 MPa·m 1 / 2 The preferred value is 1.80 MPa·m. 1 / 2 the following.

[0084] In this specification, "fracture toughness value K" IC "The determination was performed using the DCDC method [Reference: MY He, MR Turner and AG Evans, Acta Metall. Mater. 43 (1995) 3453.].

[0085] [Molten Salt]

[0086] The molten salt used in the chemically strengthened glass manufacturing method of the present invention contains sulfate ions at a rate of 1.35% by mass or more relative to the total mass of the molten salt.

[0087] The sulfate ion content in the molten salt is preferably 5.00% by mass or more, more preferably 6.00% by mass or more, and even more preferably 7.00% by mass or more, relative to the total mass of the molten salt. Furthermore, the sulfate ion content in the molten salt is preferably 24.00% by mass or less, more preferably 20.00% by mass or less, even more preferably 17.00% by mass or less, and particularly preferably 15.00% by mass or less, relative to the total mass of the molten salt.

[0088] In addition, the value of sulfate ion content in the molten salt is set as C. SO4 When the temperature of the molten salt is set to T, it is preferable to satisfy the following equation (1).

[0089] Equation (1) 0.0215T-4.0124≤C SO4 ≤0.0720T-8.4000

[0090] In equation (1), the unit of T is °C. It should be noted that the value of T is above 200.

[0091] In equation (1), C SO4 The unit is mass%, C SO4 The value is the content of sulfate ions relative to the total mass of the molten salt.

[0092] In addition, the value of sulfate ion content in the molten salt is set as C. SO4 When the temperature of the molten salt is set to T, it is more preferable to satisfy the following equation (2).

[0093] Equation (2) 0.0300T-5.6174≤C SO4 ≤0.0660T-7.7000

[0094] Furthermore, the value of sulfate ion content in the molten salt is set as C. SO4 When the temperature of the molten salt is set to T, it is more preferable to satisfy the following equation (3).

[0095] Equation (3) 0.0429T-8.0249≤C SO4 ≤0.0600T-7.0000

[0096] In equations (2) and (3), the unit of T is °C. It should be noted that the value of T is above 200.

[0097] In equations (2) and (3), C SO4 The unit is mass%, C SO4 The value is the content of sulfate ions relative to the total mass of the molten salt.

[0098] The sulfate ion content in the molten salt was analyzed using barium chloride turbidimetry. Specifically, a DPR reagent (DPR-SO4) for water quality meters manufactured by Kyoritsu Chemical Research Institute and a DPM2-SO4 digital packaging tester manufactured by Kyoritsu Chemical Research Institute were used. It should be noted that, if the salt used in the preparation of the molten salt is known, the sulfate ion content can also be calculated from the mass ratio of that salt.

[0099] The molten salts mentioned above typically contain salts with both anions and cations.

[0100] In addition to sulfate ions, the anions contained in molten salts can be, for example, selected from one or more of the group consisting of nitrate ions, nitrite ions, sulfite ions, carbonate ions, phosphate ions, and halide ions.

[0101] That is, the molten salt preferably comprises sulfate and one or more salts selected from the group consisting of nitrates, nitrites, sulfites, carbonates, phosphates and halides. Additionally, the molten salt preferably comprises nitrates and sulfates.

[0102] It should be noted that, for example, "nitrate" refers to a salt that contains nitrate ions as anions.

[0103] Examples of cations contained in the molten salt include one or more selected from the group consisting of lithium (Li) ions, sodium (Na) ions and potassium (K) ions, and more preferably two or more selected from the group consisting of lithium ions, sodium ions and potassium ions.

[0104] That is, the molten salt preferably includes one or more salts selected from the group consisting of lithium salts, sodium salts and potassium salts, and more preferably includes two or more salts selected from the group consisting of lithium salts, sodium salts and potassium salts.

[0105] It should be noted that, for example, "lithium salt" refers to a salt that contains lithium ions as cations.

[0106] Specific salts contained in the above-mentioned molten salts can be listed as those selected from the group consisting of lithium nitrate (LiNO3), sodium nitrate (NaNO3), potassium nitrate (KNO3), lithium sulfate (Li2SO4), sodium sulfate (Na2SO4), and potassium sulfate (K2SO4).

[0107] The molten salt comprises two or more salts selected from the group consisting of lithium nitrate, sodium nitrate and potassium nitrate, and more preferably comprises one or more salts selected from the group consisting of sodium sulfate and potassium sulfate.

[0108] In addition, the sulfates mentioned above preferably include at least one selected from the group consisting of lithium sulfate, sodium sulfate and potassium sulfate.

[0109] One preferred method for molten salts is to include molten salts containing sodium nitrate, potassium nitrate, and sodium sulfate.

[0110] Furthermore, when the molten salt contains sodium nitrate, the ratio of potassium nitrate content to sodium nitrate content (potassium nitrate / sodium nitrate) by mass is preferably 0.00 to 24.00, more preferably 0.00 to 9.00, even more preferably 0.25 to 4.00, and particularly preferably 0.42 to 2.34.

[0111] The molten salt mentioned above may contain lithium atoms (lithium salt).

[0112] When the molten salt contains lithium atoms, the lithium atom content relative to the total mass of the molten salt is preferably 1 ppm or more by mass, more preferably 10 ppm or more by mass, and even more preferably 100 ppm or more by mass. Furthermore, when the molten salt contains lithium atoms, the lithium atom content relative to the total mass of the molten salt is preferably 50,000 ppm or less by mass, more preferably 20,000 ppm or less by mass, and even more preferably 10,000 ppm by mass.

[0113] It should be noted that the chemically strengthened glass manufacturing method of the present invention is useful in that it can efficiently obtain chemically strengthened glass even when ions contained in the chemically strengthened glass (e.g., lithium ions in a molten salt containing sodium nitrate and sodium ions in a molten salt containing potassium nitrate) dissolve and are contained in the molten salt.

[0114] Specific components of a molten salt include, for example, a first molten salt containing potassium nitrate, sodium nitrate, lithium nitrate, and sodium sulfate.

[0115] In the first molten salt, the content of potassium nitrate is preferably 0.0% to 96.0% by mass, more preferably 20.0% to 80.0% by mass, and even more preferably 30.0% to 70.0% by mass.

[0116] In the first molten salt, the sodium nitrate content is preferably 4.0% to 100.0% by mass, more preferably 20.0% to 80.0% by mass, and even more preferably 30.0% to 70.0% by mass.

[0117] In the first molten salt, the lithium nitrate content is preferably 0.0% to 10.0% by mass, more preferably 0.01% to 5.0% by mass.

[0118] In the first molten salt, the sodium sulfate content is preferably 10.0% to 30.0% by mass, more preferably 10.0% to 20.0% by mass.

[0119] Furthermore, the molten salt used in the chemically strengthened glass manufacturing method of the present invention preferably does not contain salt in a solid state.

[0120] Molten salt, which does not actually contain salt in a solid state, refers to a state in which no precipitates are observed when molten salt is visually examined.

[0121] When the molten salt does not contain solid salt, solid salt is less likely to adhere to the surface of the chemically strengthened glass when it is lifted from the molten salt, thus suppressing appearance defects, which is therefore preferred.

[0122] Furthermore, the molten salt used in the chemically strengthened glass manufacturing method of the present invention can be a regenerated molten salt obtained by performing the molten salt regeneration treatment described later. As described below, the regenerated molten salt can be a regenerated molten salt obtained by repeating the molten salt regeneration treatment two or more times.

[0123] [Molten Salt Regeneration Process]

[0124] In the chemical strengthening glass manufacturing method (chemical strengthening treatment) of the present invention described above, the components contained in the chemically strengthening glass (e.g., lithium ions) exchange with ions in the molten salt. During the chemical strengthening treatment, the components in the chemically strengthening glass (e.g., lithium ions and sodium ions) exchange with ions contained in the molten salt, and a layer with compressive stress is formed by the difference between the ionic radii of the ions before and after the exchange.

[0125] In the molten salt after chemical strengthening treatment, the content of components (e.g., lithium ions) in the chemically strengthened glass increases. It is believed that when the content of components in the chemically strengthened glass increases in the molten salt, the aforementioned ion exchange is difficult to occur, and sometimes the chemical strengthening treatment cannot be fully carried out.

[0126] Therefore, in the chemically strengthened glass manufacturing method of the present invention, the molten salt after the chemically strengthened glass manufacturing method of the present invention is cooled, thereby precipitating a specific metal salt containing a specific metal component while maintaining the molten salt in a molten state, and performing a molten salt regeneration process to recover the specific metal salt from the molten salt in the molten state to obtain a regenerated molten salt, and immersing the chemically strengthened glass in the above-mentioned regenerated molten salt to perform a chemical strengthening process.

[0127] In this specification, "specific metal component" refers to one or more metals selected from the group consisting of lithium, sodium and potassium, preferably including lithium.

[0128] In addition, in this specification, "specific metal salt" refers to one or more metal salts selected from the group consisting of lithium salts, sodium salts and potassium salts, and lithium salts are preferred as the aforementioned specific metal salts.

[0129] The following describes the molten salt regeneration process.

[0130] In the molten salt regeneration process, the molten salt after the chemical strengthening glass manufacturing method of the present invention is cooled, thereby causing a specific metal salt containing a specific metal component to precipitate while maintaining the molten salt in a molten state, and recovering the specific metal salt from the molten salt in the molten state to obtain regenerated molten salt.

[0131] That is, the molten salt regeneration process includes: a precipitation step of cooling the molten salt to precipitate a specific metal salt containing a specific metal component while maintaining the molten salt in a molten state; and a recovery step of recovering the precipitated specific metal salt from the molten salt in a molten state.

[0132] The precipitation process and the recovery process described above will be explained below.

[0133] (Precipitation process)

[0134] In the above-mentioned molten salt regeneration process, a precipitation step is performed: the molten salt is cooled to precipitate a specific metal salt containing a specific metal component while maintaining the molten salt in a molten state.

[0135] Through a precipitation process, a specific solid metal salt is precipitated from a molten salt.

[0136] The molten salt supplied to the precipitation process is a molten salt obtained by performing a chemically strengthened glass manufacturing method. Through ion exchange, the ratio of cation content changes, but otherwise it is the same as the molten salt used in the chemically strengthened glass manufacturing method of the present invention.

[0137] The differences between the molten salt used in the chemically strengthened glass manufacturing method of the present invention described above will be explained below.

[0138] In addition, the method for performing the precipitation process thereafter is described in detail.

[0139] The molten salt supplied for the precipitation process contains specific metallic components.

[0140] The specific metal component is preferably molten in a molten salt. The specific metal component preferably includes lithium. That is, the specific metal salt precipitated in the precipitation process preferably contains lithium.

[0141] When a specific metallic component contains lithium, the molten salt preferably contains 1,000 ppm or more of lithium atoms by mass relative to the total mass of the molten salt, more preferably 2,000 ppm or more of lithium atoms by mass, and even more preferably 3,000 ppm or more of lithium atoms by mass. Furthermore, the molten salt preferably contains 30,000 ppm or less of lithium atoms by mass relative to the total mass of the molten salt, more preferably 20,000 ppm or less of lithium atoms by mass, and even more preferably 5,000 ppm or less of lithium atoms by mass.

[0142] Specific components of a molten salt include, for example, a first molten salt containing potassium nitrate, sodium nitrate, lithium nitrate, and sodium sulfate.

[0143] In the first molten salt, the content of potassium nitrate is preferably 10.0% to 96.0% by mass, more preferably 30.0% to 70.0% by mass.

[0144] In the first molten salt, the sodium nitrate content is preferably 4.0% to 90.0% by mass, more preferably 30.0% to 70.0% by mass.

[0145] In the first molten salt, the lithium nitrate content is preferably 1.0% to 50.0% by mass, more preferably 1.5% to 15.0% by mass.

[0146] In the first molten salt, the sodium sulfate content is preferably 3.0% to 30.0% by mass, more preferably 4.0% to 20.0 atoms.

[0147] In the precipitation process, the molten salt is cooled so that a specific metal salt containing a specific metal component is precipitated while the molten salt is kept in a molten state.

[0148] There are no particular restrictions on the cooling method for the molten salt in the precipitation process; known methods can be used. Furthermore, regarding the cooling of the molten salt, the entire molten salt can be cooled, or only a portion of the molten salt can be cooled.

[0149] In this case, it is preferable not to add any additives to the molten salt and instead cool the molten salt.

[0150] As an additive, it is a substance that reacts with a specific metal component to cause the precipitation of a specific metal salt. Specifically, for example, the salt contained in the molten salt mentioned above.

[0151] As a method for cooling the molten salt as a whole, examples include contacting the molten salt or the container holding the molten salt with a fluid at a temperature lower than that of the molten salt. More specifically, as the fluid mentioned above, air can be cited as an example, and methods for air cooling of the molten salt or the container holding the molten salt can be described. When air cooling of the molten salt or the container holding the molten salt, air cooling can be achieved by convection of the air in its vicinity.

[0152] Alternatively, as a method for cooling molten salt, another approach is to circulate a cooling medium within a container holding the molten salt. In this case, the container holding the molten salt preferably has a pipe through which the cooling medium circulates. The aforementioned method involves simultaneously exchanging heat with the cooling medium using a heat exchanger connected to the pipe, while simultaneously circulating the cooling medium between the container holding the molten salt and the heat exchanger.

[0153] When the molten salt is cooled as a whole, a specific metal salt containing a specific metal component precipitates from the molten salt. The specific metal salt may precipitate dispersedly in the molten salt, or it may precipitate on the wall of the container holding the molten salt, or on the surface of the apparatus described later.

[0154] Furthermore, when cooling molten salt, a portion of the molten salt can be cooled. One method for cooling a portion of the molten salt is to use an apparatus with a cooling section, bringing the cooling section into contact with the molten salt. The apparatus with the aforementioned cooling section allows for free temperature control, and when the molten salt is cooled, molten salt precipitates on the surface of the cooling section.

[0155] In this invention, the cooling of the molten salt is performed while maintaining the molten salt in a molten state. Furthermore, it is preferable that after cooling the molten salt to a predetermined temperature, that temperature is maintained for a holding time, as described later.

[0156] Regarding the cooling temperature, there are no particular limitations as long as the molten salt remains in a molten state and a specific metal salt precipitates. The preferred cooling temperature for the molten salt is 150°C or higher, more preferably 200°C or higher, and even more preferably 230°C or higher. Furthermore, the preferred cooling temperature for the molten salt is 500°C or lower, more preferably 400°C or lower, and even more preferably 350°C or lower.

[0157] Furthermore, the temperature difference between the molten salt before cooling and the molten salt after cooling is preferably 50°C or more, more preferably 100°C or more. Additionally, the aforementioned temperature difference is preferably 250°C or less, more preferably 180°C or less.

[0158] Regarding the holding time, there are no particular limitations as long as a specific metal salt precipitates; for example, 5 minutes or more, preferably 10 minutes or more, and more preferably 30 minutes or more can be listed. Furthermore, the aforementioned holding time can be, for example, 24 hours or less, preferably 12 hours or less, and more preferably 6 hours or less.

[0159] Furthermore, the temperature of the molten salt before cooling is preferably 370°C or higher, more preferably 390°C or higher. The temperature of the molten salt after cooling is preferably 360°C or lower, more preferably 330°C or lower, and even more preferably 300°C or lower. The temperatures of the molten salt before and after cooling can be appropriately adjusted according to the composition of the molten salt, etc.

[0160] In the precipitation process, the cooling of the molten salt is preferably carried out simultaneously with inducing convection in the molten salt. For example, a method for inducing convection in the molten salt can be described by stirring the molten salt with stirring blades.

[0161] By simultaneously inducing convection in the molten salt and cooling it, the molten salt can be cooled uniformly.

[0162] Examples of apparatuses for performing the precipitation process include: a container for holding molten salt, a temperature measuring unit for immersing in molten salt and measuring the temperature of the molten salt, a heating unit for heating the container for holding molten salt and heating the molten salt contained therein, and an apparatus for stirring the molten salt.

[0163] The container holding the molten salt is preferably made of a material that does not leach into the molten salt. Examples of materials that do not leach into the molten salt include metallic materials such as stainless steel, ceramic materials such as quartz glass, ceramic materials such as alumina, and heat-resistant resin materials such as tetrafluoroethylene (PTFE).

[0164] There are no particular limitations on the temperature measuring unit mentioned above; for example, well-known thermocouples can be listed.

[0165] There are no particular limitations on the heating units mentioned above; for example, heaters with electric heating wires can be listed.

[0166] In the above-described apparatus, for example, the output of the heating unit is controlled while the temperature is monitored by the temperature measuring unit, so that the molten salt can be cooled when the amount of heat input supplied from the heating unit is less than the amount of heat dissipated from the molten salt and the container holding the molten salt.

[0167] In addition, by controlling the output of the heating unit to make the heat dissipation and heat input equal, the temperature of the molten salt can be kept constant.

[0168] It should be noted that the above-mentioned device may include appliances and the like used in the recycling process described later.

[0169] (Recycling process)

[0170] In the above-mentioned molten salt regeneration process, a recovery step is performed: the specific metal salt precipitated in the above-mentioned precipitation step is recovered from the molten salt in the molten state.

[0171] Through the recycling process, a specific metal salt in solid form is separated from a liquid molten salt, and the specific metal salt containing a specific metal component is recovered. When the specific metal salt is recovered, the specific metal component (preferably containing lithium) in the molten salt is reduced.

[0172] There are no particular restrictions on the implementation method of the recycling process; well-known methods can be used.

[0173] The following describes the specific implementation method of the recycling process, but the recycling process is not limited to the following methods and various methods can be applied.

[0174] -First Implementation Method of the Recycling Process-

[0175] As one method of the recycling process, a first embodiment can be cited: when recovering a specific metal salt from molten salt in a molten state, a first device having a mesh section is used to lift the mesh section from the molten salt, thereby recovering the precipitated specific metal salt from the molten salt in a molten state.

[0176] The specific metal salt that precipitates as a solid is recovered through the mesh section of the first device and separated from the liquid molten salt.

[0177] Preferably, the first apparatus is placed in a container holding molten salt and pre-immersed in the molten salt before performing the precipitation process. If the first apparatus is placed in the container holding molten salt before performing the precipitation process, it becomes simple to lift the first apparatus and recover the specific metal salt after the precipitation process has been performed and the specific metal salt has been precipitated.

[0178] The first device described above may have a handle for lifting the mesh from the molten salt. Preferably, the handle is directly or indirectly connected to the mesh and protrudes from the surface of the molten salt, so that it can be lifted without contacting the molten salt.

[0179] It should be noted that the first apparatus described above can be immersed in molten salt after the precipitation process to recover specific metal salts.

[0180] The first appliance described above is preferably made of a material that will not dissolve into the molten salt. Examples of materials that will not dissolve into the molten salt include stainless steel and other metallic materials, quartz glass, alumina and other ceramic materials, and heat-resistant resin materials such as tetrafluoroethylene (PTFE).

[0181] Regarding the mesh section of the first device mentioned above, there are no particular restrictions as long as it can recover the specific metal salt. It can be appropriately selected according to the size of the precipitated particles of the specific metal salt. For example, the mesh size of the mesh section is preferably 0.05mm to 0.2mm.

[0182] The mesh portion of the first apparatus is preferably shaped to fit the container holding the molten salt.

[0183] -Second Implementation Method of the Recycling Process-

[0184] As another method of the recycling process, a second embodiment can be listed: cooling a molten salt containing a specific metal component, thereby causing a specific metal salt containing a specific metal component to precipitate while maintaining the molten salt in a molten state, causing the specific metal salt to precipitate onto the surface of the salt precipitation section of a second apparatus having a salt precipitation section, lifting the salt precipitation section from the molten salt, and recovering the specific metal salt from the molten salt in a molten state.

[0185] Because a specific metal salt is precipitated into the salt precipitation section of the second apparatus, when the second apparatus is lifted from the molten salt, the specific metal salt precipitated in solid form is separated from the liquid molten salt, and the specific metal salt containing the specific metal component is recovered.

[0186] During the precipitation process described above, the second apparatus is placed inside a container holding molten salt and immersed in the molten salt.

[0187] There are no particular limitations on the salt-precipitating section of the second device, but it is preferable to have a large surface area. The structure of the salt-precipitating section can be a known structure, such as a structure in which plate-like structures are arranged at predetermined intervals in a direction orthogonal to their main surface and connected to each other, or a structure in which a plate is bent into a corrugated tube (cone) shape.

[0188] The aforementioned plate-like structure or plate may have holes. Furthermore, the aforementioned plate-like structure or plate is preferably a metal plate. That is, the aforementioned plate-like structure or plate is preferably perforated metal. In addition, the aforementioned plate-like structure or plate may also undergo a roughening treatment.

[0189] Alternatively, the aforementioned plate-like structure or plate can also be a mesh made of metal wire. The mesh size is preferably 0.5 mm to 2.0 mm.

[0190] The presence of minute irregularities on the surface of the appliance promotes salt precipitation, making it a preferred choice.

[0191] The second device described above may have a handle for lifting the mesh from the molten salt. Preferably, the handle is directly or indirectly connected to the mesh, protruding from the surface of the molten salt, and can be lifted without contacting the molten salt.

[0192] The second device described above is preferably made of a material that will not dissolve into the molten salt. Examples of preferred materials are the same as those for the first device.

[0193] -Third Implementation Method of the Recycling Process-

[0194] As another method of the recycling process, a third embodiment can be listed: when cooling a molten salt containing a specific metal component, thereby causing a specific metal salt containing a specific metal component to precipitate while maintaining the molten salt in a molten state, a third device with a cooling section that is freely temperature-controlled is used to cool the molten salt by changing the temperature of the cooling section, causing the specific metal salt to precipitate onto the surface of the cooling section, lifting the cooling section from the molten salt, and recovering the specific metal salt from the molten salt in a molten state.

[0195] When the molten salt is cooled by the cooling section of the aforementioned third apparatus, the temperature of the molten salt surrounding the cooling section decreases more easily, and a specific metal salt is easily precipitated on the surface of the cooling section. When the third apparatus on which the specific metal salt has precipitated is lifted from the molten salt, the specific metal salt precipitated in solid form separates from the liquid molten salt, and the specific metal salt containing the specific metal component is recovered.

[0196] There are no particular restrictions on the cooling unit of the third appliance; for example, a structure with internal pipes through which cooling medium can flow can be cited. There are no particular restrictions on the cooling medium; known cooling media can be used. Furthermore, there are no particular restrictions on the cooling method of the cooling medium.

[0197] The cooling section can be configured such that a mesh made of metal plates or wires is connected to a pipe through which a cooling medium can flow. When the cooling section has a metal plate or the aforementioned mesh, it is easy to effectively precipitate a specific metal salt in that section.

[0198] The third device described above is preferably made of a material that will not dissolve into the molten salt. Examples of preferred materials are the same as those for the first device.

[0199] -Fourth Implementation Method of the Recycling Process-

[0200] As another method of the recycling process, a fourth embodiment can be listed: When recovering a specific metal salt from molten salt in a molten state, a molten salt holding container for containing molten salt, a circulation path connected to the molten salt holding container and allowing the molten salt discharged from the molten salt holding container to return to the molten salt holding container, and a filter disposed in the middle of the circulation path and capable of separating solids from molten salt are used to introduce molten salt containing precipitated specific metal salt into the circulation path, separate the specific metal salt from the molten salt through the filter, and recover the specific metal salt from the filter.

[0201] The above-mentioned filter can separate specific metal salts from molten salts and recover specific metal salts from the filter.

[0202] In this fourth embodiment, a circulation unit is provided in the circulation path connected to the molten salt container to circulate the molten salt, conveying the molten salt from one end of the circulation path to the other. When the aforementioned filter is installed in this circulation path, the precipitated specific metal salts are captured by the filter.

[0203] Some or all of the molten salt is discharged from the above circulation path, and specific metal salts are recovered when the filter is removed from the circulation path.

[0204] There are no particular restrictions on the above-mentioned loop unit; any known unit can be used.

[0205] Examples of filters described above include sintered metal filters, ceramic filters, and stainless steel mesh filters. The pore size of the filter can be adjusted appropriately based on the specific metal salt to be precipitated. The filter and circulation path are preferably made of a material that will not dissolve into the molten salt. Examples of preferred materials are the same as those for the first apparatus.

[0206] Alternatively, the specific metal salt recovered in the first to fourth embodiments described above can be heated at a temperature higher than the melting point of the molten salt from which the specific metal salt precipitates.

[0207] The above-mentioned temperature is preferably higher than the temperature at which the specific metal salt precipitates but lower than the temperature of the molten salt before the precipitation process. Furthermore, the above-mentioned temperature is preferably 10°C to 150°C higher than the temperature at which the specific metal salt precipitates.

[0208] When heated within the preferred temperature range described above, the constituent components of the molten salt precipitated along with the specific metal salt can be melted and removed from the specific metal salt, thereby increasing the content of the specific metal component contained in the specific metal salt.

[0209] As described above, the specific metal salts recovered in the above-described recycling process contain specific metal components.

[0210] As described above, the specific metal component preferably includes lithium. Hereinafter, preferred embodiments of the case in which lithium is included as a specific metal component will be described in a representative manner.

[0211] When a particular metal salt contains lithium, the particular metal salt is preferably a lithium sulfate, more preferably a lithium and sodium sulfate.

[0212] The preferred specific metal salt containing lithium sulfate is a crystal with a crystal structure containing space group P31c, where diffraction peaks appear in the range of 30.2° to 30.5° in the X-ray diffraction pattern measured using CuKα rays. The aforementioned X-ray diffraction pattern is determined using a so-called lumped method (also known as the θ / 2θ method). Furthermore, the aforementioned angle range is within the range of 2θ.

[0213] It should be noted that during the above-described recycling process, sometimes the specific metal salt contains components other than the specific metal component. In this case, the molten salt regeneration process may include a step after the recycling process to add the components contained in the recycled specific metal salt to the molten salt to adjust the composition of the molten salt.

[0214] That is, in the molten salt regeneration method of the present invention, the composition of the molten salt can be further adjusted after recovering specific metal components from the chemically strengthened molten salt.

[0215] When adjusting the composition of the molten salt, it is preferable to add sulfates. Furthermore, it is preferable to add components containing sodium salts, and more preferably to add components containing sodium sulfate.

[0216] Furthermore, depending on the component being recovered as a specific metal salt, components other than sulfate (preferably sodium sulfate) can be added. Examples of such components include one or more selected from the group consisting of sodium nitrate, potassium nitrate, and potassium sulfate. Moreover, by adjusting the ratio of sodium sulfate to the aforementioned components according to the component being recovered as a specific metal salt, the composition of the molten salt can be kept approximately constant.

[0217] As described above, when performing molten salt regeneration treatment, the specified composition can be maintained by reducing the content of a specific metal component (lithium) in the molten salt while also including a process that adjusts the composition of the molten salt.

[0218] Therefore, when molten salt regeneration is performed, the molten salt can be reused without replacing the molten salt supplied for chemical strengthening.

[0219] That is, chemically strengthened glass can be immersed in regenerated molten salt obtained by molten salt regeneration treatment to perform chemical strengthening treatment, and the regenerated molten salt obtained can be subjected to the above-mentioned molten salt regeneration treatment and the above-mentioned chemical strengthening treatment alternately.

[0220] The molten salt regeneration process can be performed once or more than twice. Furthermore, as described later, it is preferable to analyze the composition of the molten salt after the molten salt regeneration process. If the composition meets the aforementioned criteria, the molten salt is then subjected to chemical strengthening treatment; if the composition does not meet the aforementioned criteria, the molten salt regeneration process is performed again.

[0221] It should be noted that the method of chemically strengthening glass immersion in molten salt for chemical strengthening treatment in the chemically strengthened glass manufacturing method of the present invention is not particularly limited, and known methods can be used. Furthermore, the conditions of the chemical strengthening treatment can be appropriately adjusted according to the chemically strengthened glass and molten salt used.

[0222] For example, as a chemical strengthening treatment, the chemically strengthened glass can be immersed in a molten salt heated to 360°C to 600°C for 0.1 hours to 500 hours. It should be noted that the heating temperature of the molten salt is preferably 375°C or higher, and more preferably 500°C or lower. The immersion time of the glass plate in the molten salt is preferably 0.3 hours or higher, and more preferably 200 hours or lower.

[0223] Furthermore, chemical strengthening treatment can be performed once, or it can be performed multiple times under two or more different conditions (multi-step strengthening). Chemical strengthening treatment can be performed in one step, but it is preferable to perform two or more steps. That is, chemical strengthening treatment can use two or more molten salts with different compositions.

[0224] It should be noted that chemical strengthening treatment can be repeatedly performed using molten salt. That is, other types of chemically strengthened glass can be further impregnated in molten salt that has been used to impregnate chemically strengthened glass more than once to perform chemical strengthening treatment.

[0225] When repeatedly performing chemical strengthening treatment, it is preferable to analyze the composition of the molten salt after chemical strengthening treatment. If the composition meets the prescribed criteria, the molten salt is then subjected to chemical strengthening treatment again. If the composition does not meet the prescribed criteria, the aforementioned molten salt regeneration treatment is performed. Examples of the prescribed criteria include the content of components (e.g., lithium ions) contained in a specific metal salt recovered during the aforementioned molten salt regeneration treatment.

[0226] When analyzing the lithium ion content as the benchmark specified above, the benchmark is preferably determined as follows: the lithium ion content relative to the total mass of the molten salt is a specified value or less. For example, the lithium ion content relative to the total mass of the molten salt is preferably 200 ppm to 50,000 ppm, more preferably 2,000 ppm to 20,000 ppm, and even more preferably 3,000 ppm to 10,000 ppm.

[0227] It should be noted that when two or more molten salts with different compositions are used in chemical strengthening treatment, it is preferable to check whether the above-mentioned criteria are met to determine whether to supply the salt for chemical strengthening treatment again or to carry out molten salt regeneration treatment.

[0228] In the chemically strengthened glass manufacturing method of the present invention, when alternating between the above-described chemical strengthening treatment and molten salt regeneration treatment, the alternation can be performed once or more, or repeated more than twice. Through molten salt regeneration treatment, semi-permanent use is possible without replacing the molten salt.

[0229] Furthermore, in the chemically strengthened glass manufacturing method of the present invention, a specific metal salt or a substance obtained by processing the specific metal salt recovered in the above-mentioned recycling process can be used as a raw material to manufacture chemically strengthened glass, and the chemically strengthened glass can be supplied to the chemically strengthened glass manufacturing method of the present invention.

[0230] That is, it is preferable to use the specific metal salt recovered in the above-mentioned molten salt regeneration process as a raw material to manufacture chemically strengthened glass, and then supply the chemically strengthened glass to the chemical strengthening process. When using the specific metal salt recovered in the molten salt regeneration process as a raw material to manufacture chemically strengthened glass, it is preferable to effectively utilize the components transferred to the molten salt through the chemical strengthening process.

[0231] Chemically strengthened glass

[0232] The chemically strengthened glass of the present invention can be described in the first and second embodiments.

[0233] The method will be explained below.

[0234] [First Implementation Method]

[0235] In a first embodiment of the chemically strengthened glass of the present invention, the hydrogen concentration at a depth of 0.5 μm, measured from the outermost surface of the chemically strengthened glass, is set as C. H (0.5) Set the hydrogen concentration at a depth of 0.98 μm as C. H When (0.98), R is calculated by the following formula (H1). H It is below 2.00.

[0236] Formula (H1) R H =C H (0.5) / C H (0.98)

[0237] In equation (H1), C H (0.5) and C H The units of (0.98) are 10 20 atoms / cm 3 .

[0238] That is, in the first embodiment of the chemically strengthened glass of the present invention, the hydrogen concentration at a depth of 0.5 μm is less than 2.00 times the hydrogen concentration at a depth of 0.98 μm.

[0239] The hydrogen concentration at a specified depth, measured from the outermost surface, of the aforementioned chemically strengthened glass can be determined using secondary ion mass spectrometry (SIMS). It should be noted that SIMS allows analysis to be performed simultaneously with surface cutting via ion irradiation, thus enabling the determination of the hydrogen concentration at a specified depth.

[0240] In this invention, the hydrogen concentration was determined using SIMS-7f (manufactured by CAMECA). The SIMS measurement conditions used were Cs. +For primary ion detection, the accelerating voltage is 15.0 kV. For secondary ion detection, the detection area is set to 30 μmΦ, and negatively polar secondary ions are detected. A neutralization gun is used in this case. It should be noted that to ensure measurement accuracy, it is preferable to maintain a high vacuum within the apparatus.

[0241] In addition, the sputtering rate of ions was measured beforehand, and the sputtering time was converted into depth.

[0242] In this invention, the hydrogen concentration is determined by measuring the hydrogen concentration in a standard sample with a known hydrogen concentration. 1 H - / 30 Si - The depth-direction distribution of the intensity ratio and the chemically strengthened glass being measured. 1 H - / 30 Si - The intensity ratio is determined by comparing the depth-direction distribution.

[0243] The hydrogen concentration in the above standard sample was determined according to the following operating steps.

[0244] First, a portion of the glass plate to be measured is cut out. Then, an area of ​​50 μm or more from the surface of the cut glass plate is removed by grinding or chemical etching. This removal process is performed on both sides; that is, the thickness of the removed portion on both sides is 100 μm or more. The glass plate after this removal process is used as a standard sample.

[0245] Infrared spectroscopy (IR) was performed on the obtained standard sample to determine the IR spectrum at 3550 cm⁻¹. -1 The absorbance height A of the nearby peak 3550 and 4000cm -1 absorbance height A 4000 (Baseline). Next, the thickness d (cm) of the standard sample was measured using a micrometer and other plate thickness measuring instruments. Then, referring to reference A, the actual infrared absorption coefficient ε of H₂O in the glass was calculated. pract [L / (mol·cm)] is set to 75. The hydrogen concentration of the standard sample (converted to H2O, mol / L) is calculated using the following formula (II).

[0246] Hydrogen concentration of standard sample = (A 3550 -A 4000 ) / (ε pract ·d)…Formula (II)

[0247] Literature A) S. Ilievski et al., Glastech. Ber. Glass Sci. Technol., 73(2000)39.39

[0248] The first embodiment of the chemically strengthened glass of the present invention is obtained by the chemically strengthened glass manufacturing method of the present invention described above.

[0249] As described above, in the chemically strengthened glass manufacturing method of the present invention, the sulfate ion content of the molten salt used for chemical strengthening is a predetermined amount or more. It is believed that sulfate ions strongly attract hydrogen ions contained in the molten salt, and that sulfate ions inhibit the introduction of hydrogen ions (hydrogen) into the chemically strengthened glass. As a result, it is anticipated that chemically strengthened glass satisfying the hydrogen concentration requirement specified in the first embodiment of the chemically strengthened glass of the present invention can be obtained.

[0250] In the above formula (H1), C H The value of (0.5) is mostly 0.30 or more, preferably 0.40 or more, and more preferably 0.50 or more. In addition, the above values ​​are mostly 1.50 or less, preferably 1.20 or less, and more preferably 1.00 or less.

[0251] In the above formula (H1), C H The value of (0.98) is mostly 0.10 or higher, preferably 0.20 or higher, and more preferably 0.50 or higher. In addition, the above value is mostly 1.20 or lower, preferably 1.00 or lower, and more preferably 0.80 or lower.

[0252] R obtained from the above equation (H1) H The values ​​are mostly 0.10 or higher, preferably 0.50 or higher, and more preferably 0.80 or higher. Additionally, the aforementioned R... H The value of in the first embodiment of chemically strengthened glass is 2.00 or less, preferably 1.50 or less, and more preferably 1.20 or less.

[0253] [Second Implementation]

[0254] In a second embodiment of the chemically strengthened glass of the present invention, the hydrogen concentration at a depth of 0.6 μm, measured from the outermost surface of the chemically strengthened glass, is set as C. H (0.6) Set the hydrogen concentration at a depth of 0.8 μm as C. H When (0.8), S is calculated by the following formula (H2). H It is above -0.40.

[0255] Formula (H2) S H =(C H (0.8)-C H(0.6)) / 0.2

[0256] In equation (H2), C H (0.8) and C H The units of (0.6) are 10. 20 atoms / cm 3 .

[0257] That is, it can be said that the change in hydrogen concentration in the depth direction of the second embodiment of the chemically strengthened glass of the present invention is gradual.

[0258] In addition, the above S H The value of is typically below 0.00, and preferably below -0.10. Additionally, the above-mentioned S... H The value is -0.40 or higher, preferably -0.35 or higher, and more preferably -0.30 or higher.

[0259] In a second embodiment of the chemically strengthened glass of the present invention, the hydrogen concentration at a predetermined depth measured from the outermost surface of the chemically strengthened glass can also be determined by secondary ion mass spectrometry (SIMS). Details regarding the determination method using SIMS are as described in the first embodiment and are therefore omitted here.

[0260] The second embodiment of the chemically strengthened glass of the present invention is obtained by the chemically strengthened glass manufacturing method of the present invention described above.

[0261] As described above, in the chemically strengthened glass manufacturing method of the present invention, the sulfate ion content of the molten salt used for chemical strengthening is a predetermined amount or more. As described above, it is believed that when chemical strengthening is performed using a molten salt containing sulfate ions, the introduction of hydrogen ions (hydrogen) into the chemically strengthened glass is suppressed. As a result, it is anticipated that chemically strengthened glass satisfying the requirements related to the hydrogen concentration specified in the second embodiment of the chemically strengthened glass of the present invention can be obtained.

[0262] In the above formula (H2), C H The value of (0.8) is mostly 0.10 or higher, preferably 0.20 or higher, and more preferably 0.50 or higher. In addition, the above values ​​are mostly 1.00 or lower, preferably 0.90 or lower, and more preferably 0.80 or lower.

[0263] In the above formula (H2), C H The value of (0.6) is mostly 0.10 or more, preferably 0.20 or more, and more preferably 0.50 or more. In addition, the above values ​​are mostly 1.20 or less, preferably 1.00 or less, and more preferably 0.80 or less.

[0264] [Compressive stress]

[0265] The chemically strengthened glass of the present invention (first and second embodiments, hereinafter the same) mostly has a compressive stress layer on the surface side where compressive stress acts. Hereinafter, preferred parameters related to compressive stress will be described.

[0266] It should be noted that in this specification, "stress distribution" is a graph representing compressive stress values ​​using depth measured from the glass surface as the variable. Negative compressive stress values ​​refer to tensile stress.

[0267] In this specification, the "stress distribution" can be determined by combining an optical waveguide surface stress meter and a scattered light photoelastic stress meter.

[0268] Optical waveguide surface stress gauges can accurately measure the stress near a glass surface in a short time. An example of an optical waveguide surface stress gauge is the FSM-6000 manufactured by Orihara Seisakusho.

[0269] On the other hand, the method of using a scattered light photoelastic stress meter can measure the stress inside the glass. For example, there is the SLP-2000 manufactured by Orihara Seisakusho Co., Ltd.

[0270] This manual describes the use of two measuring devices in combination: an optical waveguide surface stress gauge and a scattered light photoelastic stress gauge, to perform accurate stress measurements.

[0271] In addition, in this specification, the compressive stress layer depth refers to the depth where the compressive stress value is zero.

[0272] The compressive stress (CS0) on the outermost surface of the chemically strengthened glass of the present invention is preferably 50 MPa or more, more preferably 100 MPa or more, and even more preferably 150 MPa or more. The CSO of the chemically strengthened glass of the present invention is mostly 1500 MPa or less, preferably 1000 MPa or less, more preferably 800 MPa or less, and even more preferably 600 MPa or less.

[0273] The CSO of the chemically strengthened glass of the present invention is measured using an optical waveguide surface stress meter.

[0274] For the compressive stress (CS) at a depth of 50 μm in the chemically strengthened glass of this invention 50 From the viewpoint that the chemically strengthened glass of the present invention is not prone to breakage even under greater impact when it collides with other objects, the pressure is preferably 0 MPa or more, more preferably 30 MPa or more, and even more preferably 50 MPa or more. Furthermore, the CS of the chemically strengthened glass of the present invention... 50 Most of them are below 600MPa, preferably below 500MPa, more preferably below 400MPa, even more preferably below 350MPa, and may also be below 200MPa.

[0275] The compressive stress at each of the above depths can be obtained by calculating the stress distribution using the above method.

[0276] The compressive stress layer depth (DOC) of the chemically strengthened glass of the present invention is preferably 30 μm or more, more preferably 50 μm or more, and even more preferably 80 μm or more. The DOC of the chemically strengthened glass of the present invention is preferably 300 μm or less, more preferably 250 μm or less, and even more preferably 200 μm or less.

[0277] [Tensile stress]

[0278] Most of the chemically strengthened glass of the present invention has a compressive stress layer on the surface, at which point the tensile stress that balances it inside the chemically strengthened glass takes effect.

[0279] The preferred parameters related to tensile stress are explained below.

[0280] The maximum tensile stress (CT) of the chemically strengthened glass of this invention Max Preferably, the pressure is 30 MPa or higher, more preferably 40 MPa or higher, and even more preferably 100 MPa or higher. Furthermore, the CT of the chemically strengthened glass of the present invention... Max Most are below 300MPa, preferably below 250MPa, and more preferably below 220MPa.

[0281] CT Max Determined from the stress distribution, it typically acts at the center of the plate thickness.

[0282] The average tensile stress (CT) of the chemically strengthened glass of this invention ave Preferably, the pressure is 30 MPa or higher, more preferably 50 MPa or higher, and even more preferably 95 MPa or higher. Furthermore, the CT of the chemically strengthened glass of the present invention... ave Most are below 200MPa, preferably below 150MPa.

[0283] The average value of tensile stress is obtained by dividing the integral value of the tensile stress in the thickness direction of the plate by the length of the tensile stress region in the stress distribution, representing the depth of the tensile stress.

[0284] The integral value of tensile stress (ICT) of the chemically strengthened glass of the present invention is mostly 70,000 Pa·m or less, preferably 60,000 Pa·m or less, and more preferably 55,000 Pa·m or less. There is no particular limitation on the lower limit of ICT, but it is mostly 10,000 Pa·m or more, preferably 20,000 Pa·m or more.

[0285] ICT is obtained by integrating the tensile stress over a region representing the depth of the tensile stress.

[0286] [Plate thickness]

[0287] The thickness of the chemically strengthened glass of the present invention (first embodiment and second embodiment) can be appropriately adjusted according to the application, and is mostly 0.1 mm or more, preferably 0.2 mm or more, more preferably 0.3 mm or more, and even more preferably 0.4 mm or more. In addition, the thickness of the chemically strengthened glass of the present invention is mostly 2.0 mm or less, preferably 1.5 mm or less, more preferably 1.2 mm or less, and even more preferably 1.0 mm or less.

[0288] [composition]

[0289] The chemically strengthened glass of the present invention (first embodiment and second embodiment) is obtained by chemically strengthening a plate-shaped glass (glass for chemical strengthening) before chemical strengthening.

[0290] The glass composition of the chemically strengthened glass is consistent with the composition at the center of the thickness of the chemically strengthened glass sheet. That is, the preferred composition at the center of the thickness of the chemically strengthened glass sheet is consistent with the preferred composition of the chemically strengthened glass.

[0291] The preferred composition of the chemically strengthened glass is described in the same manner as in the part about the chemically strengthened glass manufacturing method of the present invention, and therefore the description is omitted.

[0292] [use]

[0293] The chemically strengthened glass of the present invention (first embodiment and second embodiment) exhibits high drop strength and can therefore be applied to a variety of uses.

[0294] For example, the chemically strengthened glass of the present invention is useful as a protective glass.

[0295] The aforementioned protective glass can also be used for surface protection purposes such as displays and solar cell modules.

[0296] In particular, the chemically strengthened glass of the present invention is useful as protective glass for mobile devices such as mobile phones, smartphones, portable information terminals (PDAs), and tablet terminals. Furthermore, it is also useful for protective glass for display devices such as televisions (TVs), personal computers (PCs), and touch panels that are not intended for portability; protective glass for the surface of solar cell modules; building materials such as elevator walls, walls of buildings (full-screen displays) such as houses and buildings, and window glass; and interior decorations for desktops, automobiles, and aircraft. Additionally, it is useful as protective glass for the aforementioned items. Furthermore, through bending processing and bending forming, it can also be applied to applications such as housings with curved shapes.

[0297] Example

[0298] The present invention will now be described in more detail based on embodiments.

[0299] The materials, quantities, proportions, processing contents, and processing steps shown in the following embodiments can be appropriately modified without departing from the spirit of the invention. Therefore, the scope of the invention should not be interpreted as limited by the embodiments shown below.

[0300] It should be noted that, in this embodiment, the surface compressive stress of the chemically strengthened glass was measured using a scattered light photoelastic stress meter (SLP). The SLP used was the SLP-2000 manufactured by Orihara Seisakusho Co., Ltd.

[0301] Hereinafter, Examples 2, 4, 6 to 11, 13, 15 and 18 to 20 are examples, and Examples 1, 3, 5, 12, 14, 16 and 17 are comparative examples.

[0302] <Example 1>

[0303] First, prepare a molten salt with the following composition.

[0304] Potassium nitrate: 50.0% by mass

[0305] • Lithium nitrate: 2.5% by mass

[0306] Sodium nitrate: 47.5% by mass

[0307] Chemically strengthened glass is obtained by impregnating a prepared molten salt with the following composition. It should be noted that the composition of the chemically strengthened glass below is in molten percentage (mol%) based on oxides.

[0308] SiO2: 66.2%

[0309] Al2O3: 11.2%

[0310] MgO: 3.1%

[0311] CaO: 0.2%

[0312] TiO2: 0.1%

[0313] ZrO2: 1.3%

[0314] Y2O3: 0.5%

[0315] Li2O: 10.4%

[0316] Na2O: 5.6%

[0317] K2O: 1.5%

[0318] In Example 1, chemical strengthening treatment was performed on the chemically strengthened glass with the above composition under the following conditions. The surface compressive stress of the obtained chemically strengthened glass was measured by the above method, and the compressive stress value CS50 at a depth of 50 μm from the surface was measured. The results are shown in the table below.

[0319] • Chemical strengthening temperature: 410℃

[0320] • Chemical fortification time: 120 minutes

[0321] <Example 2 to Example 16>

[0322] The chemical strengthening process was performed in the same manner as in Example 1, except that the molten salt used for chemical strengthening was changed to the molten salt with the composition shown in the table below.

[0323] In addition, the surface compressive stress of the chemically strengthened glass was measured using the same method as in Example 1. The results are shown in the table below.

[0324] <Evaluation>

[0325] For each of the chemically strengthened glass samples obtained, the drop strength was evaluated according to the following procedures.

[0326] A simulated smartphone was created by embedding chemically strengthened glass into a structure with the mass and rigidity adjusted to the size of a typical smartphone currently in use. The simulated smartphone was then dropped freely onto #180 SiC sandpaper, with the side containing the chemically strengthened glass facing the ground, while varying the height. Regarding the drop height, it was first dropped from a height of 5 cm. If the chemically strengthened glass did not break after the 5 cm drop, it was dropped from a height of 10 cm. Furthermore, if the chemically strengthened glass did not break after the 10 cm drop, it was dropped from a height of 15 cm. This process was repeated, dropping from a position 5 cm higher than the previous drop height, until the chemically strengthened glass broke. The height at which the chemically strengthened glass first broke during the above steps was taken as the drop height.

[0327] For the aforementioned drop height, measurements were taken on 19 pieces of tempered glass, and the arithmetic mean of the drop heights was presented as the drop height in the table below.

[0328] It should be noted that the greater the drop height value, the less likely the chemically strengthened glass will break even when dropped from a higher position; that is, it has higher drop strength.

[0329] <Results>

[0330] The composition of the molten salt used in Examples 1 to 16 above, the compressive stress value of the chemically strengthened glass obtained, and the above evaluation results are shown in Table 1.

[0331] It should be noted that in Table 1, the "KNO3 / LiNO3" column represents the mass ratio of potassium nitrate content to lithium nitrate content in the molten salt.

[0332] Table 1

[0333] Based on the results shown in Table 1, when comparing examples of molten salts with similar compositions (refer to "KNO3 / LiNO3"), it was confirmed that chemically strengthened glass with higher drop strength can be obtained when the sulfate ion content in the molten salt is above a specified amount.

[0334] More specifically, based on the comparisons between Examples 1 and 2, Examples 3 and 4, Examples 5 and 6-10, Examples 12 and 11, Examples 14 and 13, and Examples 16 and 15, it was confirmed that when comparing molten salts with the same lithium nitrate content, chemically strengthened glass with higher drop strength can be obtained when the sulfate ion content in the molten salt is above a specified amount.

[0335] It should be noted that in Example 10, the molten salt contains salt in a solid state. Sometimes the solid salt adheres to the obtained chemically strengthened glass, and sometimes it becomes a defect in appearance.

[0336] <Example 17>

[0337] First, prepare a molten salt with the following composition.

[0338] Potassium nitrate: 47.6% by mass

[0339] • Lithium nitrate: 4.8% by mass

[0340] Sodium nitrate: 47.6% by mass

[0341] The prepared molten salt is impregnated with a chemically strengthened glass of the following composition, thereby performing a chemical strengthening treatment to obtain chemically strengthened glass. It should be noted that the composition of the chemically strengthened glass below is based on oxides in mol% terms.

[0342] SiO2: 66.2%

[0343] Al2O3: 11.2%

[0344] MgO: 3.1%

[0345] CaO: 0.2%

[0346] TiO2: 0.1%

[0347] ZrO2: 1.3%

[0348] Y2O3: 0.5%

[0349] Li2O: 10.4%

[0350] Na2O: 5.6%

[0351] K2O: 1.5%

[0352] In Example 17, the chemically strengthened glass with the above composition was subjected to chemical strengthening treatment under the following conditions. In the obtained chemically strengthened glass, the hydrogen concentration at each depth measured from the surface was determined using the method described above, and R, obtained from the above formula (H1), was calculated. H The value of , and S obtained from the above equation (H2). H The values ​​are shown in Table 2 below.

[0353] • Chemical strengthening temperature: 410℃

[0354] • Chemical fortification time: 120 minutes

[0355] <Example 18~Example 20>

[0356] Except that the molten salt used in the chemical fortification was changed to the molten salt with the composition shown in Table 2 below, the chemical fortification treatment was carried out in the same manner as in Example 17.

[0357] In addition, the hydrogen concentration of the chemically strengthened glass obtained was determined using the same method as in Example 17, and R was calculated. H and S H The values ​​are shown in the table below.

[0358] <Results>

[0359] The composition of the molten salt used in Examples 17 to 20 above, and the R of the chemically strengthened glass obtained, are discussed. H and S H The values ​​are shown in Table 2.

[0360] Table 2

[0361] The results shown in Table 2 confirm that when the sulfate ion content in the molten salt is above a specified level, chemically strengthened glass with higher drop strength can be obtained.

[0362] More specifically, based on the comparison between Examples 17 and 18, and between Examples 17 and 20, it was confirmed that when comparing molten salts with the same lithium nitrate content, chemically strengthened glass with higher drop strength can be obtained when the sulfate ion content in the molten salt is above a specified amount.

[0363] Furthermore, it was confirmed that R, calculated from the above formula (H1), was present in the chemically strengthened glasses of Examples 18, 19, and 20. H The value is below 2.00. Furthermore, the value of S obtained from the above formula (H2) was confirmed. H The value is above -0.40.

[0364] It should be noted that the entire contents of the specification, claims and abstract of Japanese Patent Application No. 2024-043187, filed on March 19, 2024, are incorporated herein as a disclosure of the specification of this invention.

Claims

1. A method for manufacturing chemically strengthened glass, wherein the method comprises immersing chemically strengthened glass in molten salt to manufacture chemically strengthened glass, wherein... The molten salt contains sulfate ions, and the content of sulfate ions in the molten salt is 1.35% by mass or more relative to the total mass of the molten salt.

2. The method for manufacturing chemically strengthened glass according to claim 1, wherein, The molten salt comprises: sulfates, and It is selected from one or more of the group consisting of nitrates, nitrites, sulfites, carbonates, phosphates and halide salts.

3. The method for manufacturing chemically strengthened glass according to claim 2, wherein, The molten salt comprises the nitrate and the sulfate.

4. The method for manufacturing chemically strengthened glass according to claim 2, wherein, The sulfate comprises at least one selected from the group consisting of lithium sulfate, sodium sulfate, and potassium sulfate.

5. The method for manufacturing chemically strengthened glass according to any one of claims 1 to 4, wherein, The molten salt does not actually contain salt in a solid state.

6. The method for manufacturing chemically strengthened glass according to any one of claims 1 to 4, wherein, The sulfate ion content in the molten salt is 5.00% to 24.00% by mass relative to the total mass of the molten salt.

7. The method for manufacturing chemically strengthened glass according to any one of claims 1 to 4, wherein, Let the value of sulfate ion content in the molten salt be set as C. SO4 When the temperature of the molten salt is set to T, the following equation (1) is satisfied: Equation (1) 0.0215T-4.0124≤C SO4 ≤0.0720T-8.4000 In equation (1), the unit of T is °C. It should be noted that the value of T is above 200. In equation (1), C SO4 The unit is mass%, C SO4 The value is the content of sulfate ions relative to the total mass of the molten salt.

8. The method for manufacturing chemically strengthened glass according to any one of claims 1 to 4, wherein, Before and after immersing the chemically strengthened glass in the molten salt, the element with the largest increase in concentration in the molten salt is selected as the specific alkali element. The content of the specific alkali element in the molten salt is 1 ppm to 50,000 ppm by mass relative to the total mass of the molten salt.

9. The method for manufacturing chemically strengthened glass according to any one of claims 1 to 4, wherein, The molten salt comprises two or more salts selected from the group consisting of lithium, sodium, and potassium salts.

10. The method for manufacturing chemically strengthened glass according to any one of claims 1 to 4, wherein, The molten salt comprises two or more salts selected from the group consisting of lithium nitrate, sodium nitrate, and potassium nitrate. The molten salt further comprises one or more salts selected from the group consisting of sodium sulfate and potassium sulfate.

11. The method for manufacturing chemically strengthened glass according to any one of claims 1 to 4, wherein, The molten salt contains sodium nitrate, and the ratio of potassium nitrate content to sodium nitrate content by mass is 0.00 to 24.

00.

12. The method for manufacturing chemically strengthened glass according to any one of claims 1 to 4, wherein, The molten salt contains sodium nitrate, and the ratio of potassium nitrate content to sodium nitrate content is 0.25 to 9.00 by mass.

13. The method for manufacturing chemically strengthened glass according to any one of claims 1 to 4, wherein, The molten salt contains sodium nitrate, and the ratio of potassium nitrate content to sodium nitrate content by mass is 0.42 to 2.

34.

14. The method for manufacturing chemically strengthened glass according to any one of claims 1 to 4, wherein, The chemically strengthened glass contains silicon, aluminum, and lithium.

15. A method for manufacturing chemically strengthened glass, wherein, The molten salt after the chemical strengthening glass manufacturing method of claim 14 is further cooled to precipitate a specific metal salt containing lithium while maintaining the molten salt in a molten state, and then a molten salt regeneration process is performed to recover the specific metal salt from the molten salt in the molten state to obtain regenerated molten salt. Chemical strengthening is performed by immersing the chemically strengthened glass in the regenerated molten salt.

16. The method for manufacturing chemically strengthened glass according to claim 15, wherein, When obtaining the regenerated molten salt, sulfate is added to the molten salt after the specific metal salt is recovered.

17. A method for manufacturing chemically strengthened glass, wherein, The regenerated molten salt after the chemical strengthening glass manufacturing method of claim 15 is subjected to alternating molten salt regeneration treatment and chemical strengthening treatment.

18. A chemically strengthened glass, wherein, Let the hydrogen concentration at a depth of 0.5 μm, measured from the outermost surface of the chemically strengthened glass, be C. H (0.5) Set the hydrogen concentration at a depth of 0.98 μm as C. H When (0.98), R is calculated by the following formula (H1). H Below 2.00 Formula (H1) R H =C H (0.5) / C H (0.98) In equation (H1), C H (0.5) and C H The units of (0.98) are 10 20 atoms / cm 3 .

19. A chemically strengthened glass, wherein, Let the hydrogen concentration at a depth of 0.6 μm, measured from the outermost surface of the chemically strengthened glass, be C. H (0.6) Set the hydrogen concentration at a depth of 0.8 μm as C. H When (0.8), S is calculated by the following formula (H2). H Above -0.40 Formula (H2) S H =(C H (0.8)-C H (0.6)) / 0.2 In equation (H2), C H (0.8) and C H The units of (0.6) are 10. 20 atoms / cm 3 .

Citation Information

Patent Citations

  • Chemically strengthened glass

    JP2013520388A

  • Control device and control program for rotary electric machine

    JP2024043187A